A two-step multidisciplinary approach to treat recurrent esophageal strictures in children with epidermolysis bullosa dystrophica - Vowinkel, Thorsten; Laukoetter, Mike; Mennigen, Rudolf; Hahnenkamp, Klaus; Gottschalk, Antje; Boschin, Matthias; Frosch, Michael; Senninger, Norbert; Tübergen, Dirk (Endoscopy, 2015)
In children with severe generalized recessive dystrophic epidermolysis bullosa (RDEB), esophageal scarring leads to esophageal strictures with dysphagia, followed by malnutrition and delayed development. We describe a two-step multidisciplinary therapeutic approach to overcome malnutrition and growth retardation. In Step 1, under general anesthesia, orthograde balloon dilation of the esophagus is followed by gastrostomy creation using a direct puncture technique. In Step 2, further esophageal strictures are treated by retrograde dilation via the established gastrostomy; this step requires only a short sedation period. A total of 12 patients (median age 7.8 years, range 6 weeks to 17 years) underwent successful orthograde balloon dilation of esophageal strictures combined with direct puncture gastrostomy. After 12 and 24 months in 11 children, a substantial improvement of growth and nutrition was achieved (body mass index [BMI] standard deviation score [SDS] + 0.59 and + 0.61, respectively). In one child, gastrostomy was removed because of skin ulcerations after 10 days. Recurrent esophageal strictures were treated successfully in five children. The combined approach of balloon dilation and gastrostomy is technically safe in children with RDEB, and helps to promote catch-up growth and body weight. In addition, recurrent esophageal strictures can be treated successfully without general anesthesia in a retrograde manner via the established gastrostomy.